PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA RESTORAN TAMAN PRINGSEWU YOGYAKARTA - Intan Setyowati; Sri Haryani (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2016)
Employee performance will have an impact on both employee and company productivity, which in turn will affect the achievement of corporate goals. Good performance of both the employees and the company makes the leaders keep their employees performance high. In order to improve employee performance, the leaders must understand the factors that influence employee performance. This study analyzes the influence of leadership, motivation, and compensation to employee performance. Data collection was carried out by questionnaires distributed to all employees at Pringsewu Garden Restaurant in Yogyakarta. In this study, data analysis includes validity and reliability testing, hypothesis testing, classic assumption test and multiple linear regressions. Data analysis uses SPSS version 20.00. Based on test validity, all variable statement items of leadership, motivation, compensation, and performance are proven to be valid as indicated by the value of the t (Pearson correlation) > t table 0,349. For reliability test, all variable statement items of leadership, motivation, compensation, and performance are simultaneously or partially proven to be reliable. It is shown by the value of Cronbach 's Alpha > 0.06 and the value of Cronbach' s Alpha if Item Deleted > 0.06. The results of multicollinearity, heteroscedasticity, and autocorrelation classical assumption test show that there is no multicollinearity problems among the independent variables, there is no heteroscedasticity in regression models, and there is no autocorrelation. The value of adjusted R Square is 0.822 or 82.2%. It shows that 82.2% of employee performance is influenced by leadership, motivation, and compensation, while the remaining 17.8% is influenced by other variables that are not described in this study. The results of multiple linear regression equation Y = 0.617 + 0.462X1+ 0.381X2 + 0.417X3. Based on t test results, it can be concluded that the variables of leadership, motivation, and compensation partially influence employee performance. Based on F test results, it is concluded that the variables of leadership, motivation, and compensation simultaneously affect the performance of employee. Keywords : leadership, motivation, compensation, employee performance